2023
DOI: 10.1093/jee/toad145
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance and fitness cost of laboratory-selected resistance to Vip3Aa in Helicoverpa zea (Lepidoptera: Noctuidae)

Abstract: The polyphagous pest Helicoverpa zea (Lepidoptera: Noctuidae) has evolved practical resistance to transgenic corn and cotton producing Cry1 and Cry2 crystal proteins from Bacillus thuringiensis (Bt) in several regions of the United States. However, the Bt vegetative insecticidal protein Vip3Aa produced by Bt corn and cotton remains effective against this pest. To advance knowledge of resistance to Vip3Aa, we selected a strain of H. zea for resistance to Vip3Aa in the laboratory. After 28 generations of continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In another study, Carrière et al reported that a laboratory-selected Vip3Aa resistant strain of H. zea displayed autosomal and almost completely recessive resistance to Vip3Aa protein. 37 These results suggest that autosomal recessive inheritance of Vip3Aa resistance may be a common occurrence in H. zea populations, which has significant implications for insect resistance management (IRM). The current highdose refuge IRM strategy for Bt crops relies on the assumption that resistance to Bt proteins in target insects is recessive, resulting in elimination of heterozygotes by high-dose Bt plants, thereby delaying the evolution of insect resistance to Bt crops.…”
Section: Discussionmentioning
confidence: 96%
“…In another study, Carrière et al reported that a laboratory-selected Vip3Aa resistant strain of H. zea displayed autosomal and almost completely recessive resistance to Vip3Aa protein. 37 These results suggest that autosomal recessive inheritance of Vip3Aa resistance may be a common occurrence in H. zea populations, which has significant implications for insect resistance management (IRM). The current highdose refuge IRM strategy for Bt crops relies on the assumption that resistance to Bt proteins in target insects is recessive, resulting in elimination of heterozygotes by high-dose Bt plants, thereby delaying the evolution of insect resistance to Bt crops.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the presentation of the novel research results, combined with an individual perspective of the area, could add interesting features to the presented studies. Plant genetic modification by synthetic promoters is pivotal for introducing metabolic switches, and for enabling the development of novel, more efficient, or stress-resistant crop variants with outstanding characteristics or an increased biosynthesis rate of valuable metabolites [1,4,5,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Global climate change has elevated the role of sustainable agriculture; there is a growing demand for novel plant genotypes or genetically modified plants with increased tolerance to biotic and abiotic stresses or secondary metabolite production [1][2][3][4][5][6][7]. This can be enabled by the expression of foreign genes that increase resistance to insects, herbicides as glyphosate, or by facilitating biosynthesis, such as carotenes or astaxanthin in rice [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…However, up to now, there is no evidence to link those proteins with resistance to Vip3Aa selected in the laboratory or field. Although a number of Vip3Aa-resistant insect colonies have been established and the genetic of Vip3Aa resistance have been well characterized (12,13,17,18,20,30), the genetic basis associated with Vip3Aa resistance for those cases have not been reported. Recently, downregulation of a transcription factor, SfMyb, was reported to be associated with resistance to Vip3Aa in S. frugiperda (31).…”
Section: Introductionmentioning
confidence: 99%